Development of Augmented Reality-Based "KARINA" Media to Improve Learning Outcomes in Traditional Clothing Content for Grade III Students - Faiza, Irsyanda Naufal; Yulianto, Sigit (Jurnal Paedagogy, 2026)
This study aims to develop KARINA (National Interactive Card) learning media based on Augmented Reality (AR) to improve students’ learning outcomes on the topic of traditional clothing for third-grade students. The study employed a Research and Development (R&D) method adapted from the four-dimensional (4D) development model, comprising the stages of define, design, develop, and disseminate. The research involved six students in a small group test and 23 students in a large group test. Data were collected using both testing and non-testing instruments. Testing instruments included pre-tests and post-tests, while non-testing instruments consisted of interviews, questionnaires, and documentation studies. Data analysis was performed using Shapiro–Wilk tests for normality, paired-sample t-tests, and N-Gain calculations with SPSS 31. Validation results indicated that the learning media is in the very feasible category, with scores of 88% from material experts and 93% from media experts. The effectiveness of the media was demonstrated by significant improvements in learning outcomes: in the small group test, the average score increased from 57.5 to 85 (N-Gain = 0.62), while in the large group test, it increased from 67.3 to 89 (N-Gain = 0.57). Both results are categorized as quite effective. These findings indicate that AR-based Interactive Cards are effective in improving students’ conceptual understanding and learning outcomes in Pancasila Education.